A MULTIDISCIPLINARY APPROACH TO THE TREATMENT OF CHRONIC PANCREATITIS - Julia Czerwik; Katarzyna Krzemińska; Maria Kubas; Julia Kuszneruk; Joanna Dmochowska; Marta Czubala; Aleksandra Kaźmierczyk; Jędrzej Kęsik; Patrycja Felisiak; Karol Kanon (International Journal of Innovative Technologies in Social Science, 2025)
Chronic pancreatitis (CP) is a progressive inflammatory disease of the pancreas that leads to irreversible structural damage, abdominal pain, and exocrine and endocrine insufficiency. Its etiology is multifactorial, with alcohol consumption and cigarette smoking representing the most significant modifiable risk factors, while genetic, autoimmune, and metabolic mechanisms are increasingly recognized. The aim of this review was to summarize current knowledge on the pathogenesis, diagnosis, and management of CP, with particular emphasis on the importance of an interdisciplinary approach. A comprehensive literature focused on original studies, clinical guidelines, and meta-analyses published in the last 15 years. Effective management of CP requires a stepwise strategy, beginning with lifestyle modification, pain control, pancreatic enzyme replacement therapy, and management of diabetes. Endoscopic and surgical procedures are reserved for patients with refractory symptoms, with duodenum-preserving techniques demonstrating favorable outcomes in pain relief, pancreatic function preservation, and quality of life. In advanced disease, surgical management provides superior long-term results compared with endoscopy. In addition, psychological care has emerged as an integral part of management, addressing the burden of chronic pain, comorbid depression, and addictive behaviors. Nutritional support, including adequate enzyme supplementation and correction of fat-soluble vitamin deficiencies, remains essential to prevent malnutrition and osteoporosis. In conclusion, CP is a complex disorder requiring multidisciplinary care. Early recognition of risk factors, combined with individualized therapeutic strategies and integration of medical, surgical, and psychosocial interventions, is fundamental to improving patient prognosis and quality of life.